A STUDY OF MEASLES VACCINATION COVERAGE BY LOT QUALITY ASSURANCE SAMPLING TECHNIQUE AND FACTORS RELATED TO NON-VACCINATION IN BELLARY DISTRICT - Karinagannanavar, A; Khan, W; Raghavendra, B; Sameena, ARB; Goud, T G (Indian Journal of Community Health, 2013)
Background: Measles is a leading cause of childhood morbidity and mortality accounting for nearly half the global burden of vaccine preventable deaths. In 2007, there were 197000 measles deaths globally nearly 540 deaths every day or 22 deaths per hour. According to NFHS-3 2005 – 06 total measles vaccination coverage in Karnataka was 72%. Objectives: 1) To find out measles vaccination coverage in Bellary District. 2) To know the reasons for non-vaccination. Material and Methods: A Cross sectional study was conducted from May 2010 to April 2011 at areas covered by PHC/PHU of Bellary district by using Lot Quality Assurance Sampling (LQAS) method. Total sample size was 1007(53X19). Bellary district has 47 primary health centers (PHC) and 6 primary health units (PHU), all of which were studied in which each PHC/PHU is considered as a lot. The data was collected from parents of children aged 12-23 months using a pretested semi structured questionnaire. Results: Out of 53 PHC’s/PHU’s we accepted 41 (77.35%) and vaccination coverage in these lots was considered as more than 85% and overall coverage in Bellary district was 69.41% and 53.62% had received Vitamin A supplementation. The reasons for non vaccination were lack of awareness, ignorance, ill health of the child, fear of side effects & lack of health services. Conclusion: Measles vaccination coverage was 69.41% and the reasons for non vaccination were lack of awareness, ignorance, ill health of the child, fear of side effects and lack of health services.